Distinct humoral responses induced by heterologous versus homologous prime–boost immunization strategies in early life - Foroutan Pajoohian, Poorya; Aradottir Pind, Audur Anna; Molina Estupiñan, Jenny Lorena; Christensen, Dennis; Pedersen, Gabriel Kristian; Olafsdottir, Thorunn A.; Jonsdottir, Ingileif; Bjarnarson, Stefania P. (Frontiers in Immunology, 2025)
An important component in the development of efficacious vaccines is the optimization of vaccination schedules to elicit protective immunity, especially in a vulnerable group like infants. Mucosal IgA plays an important role in the initial defense at mucosal surfaces, protecting against the colonization of respiratory pathogens, potentially reducing invasion and disease severity, while systemic immunity relies on protective IgG antibodies (Abs). This study aims to design an immunization strategy inducing both optimal systemic and mucosal immune responses using heterologous prime–boost immunization in comparison to homologous immunization. We immunized neonatal mice with a pneumococcal conjugate vaccine, Pn1-CRM197, by heterologous subcutaneous (s.c.) priming with CAF01 adjuvant, followed by intranasal (i.n.) booster with multiple mutant of cholera toxin (mmCT) adjuvant or homologous immunizations by either route. Schedules including mucosal immunization, either once in heterologous s.c. priming followed by i.n. booster or twice with homologous i.n./i.n. immunization, induced higher serum and mucosal vaccine-specific IgA Abs and Ab-secreting cells (ASCs) than homologous s.c./s.c. immunization. However, heterologous s.c./i.n. immunization did not induce vaccine-specific IgG Abs in serum and the lung to a comparable level with that of homologous s.c./s.c. immunization. The immunization route in priming and boosting affected the induction of specific ASCs in lymphoid organs. Homologous s.c./s.c. immunization induced systemic (spleen) and local (inguinal lymph nodes) IgG responses. Homologous i.n./i.n. immunization induced systemic and local mucosal IgA responses, observed by enhanced salivary and lung IgA Abs. Meanwhile, heterologous s.c/i.n. immunization induced local humoral IgG and IgA responses in draining lymph nodes (cervical) and accelerated the early homing of IgG and IgA ASCs to the bone marrow compared to homologous i.n./i.n. immunization. Increasing the vaccine dose in the i.n. booster of heterologous immunization was needed to improve further humoral immune responses. Taken together, homologous s.c./s.c. immunization induces higher systemic IgG responses than heterologous s.c./i.n., which could be enhanced by increasing the vaccine dose in the i.n. booster but was still lower than after s.c./s.c. immunization. However, heterologous s.c./i.n. immunization has the advantage of inducing IgA responses, comparable to homologous i.n./i.n. immunization. This study indicates that heterologous immunization schedules may be an attractive approach for inducing early-life systemic and mucosal humoral immune responses.